The Effectiveness of Information Services in Enhancing the Sense of Purpose Among Minangkabau Adolescents: A Quasi-Experimental Study - Mega Mustika; Hermana Nirwana; Dina Sukma; Firman; Fettry Arnetty (Universitas PGRI Yogyakarta, 2026)
This study examines the effectiveness of information services in enhancing the sense of purpose among Minangkabau adolescents, which represents an essential aspect of psychological well-being and educational functioning. A quasi-experimental one-group pretest–posttest design was applied with a sample of 104 high school students selected through stratified random sampling. Data on meaning in life were collected using the Meaningfulness of Life Checklist and analyzed using paired and independent sample t-tests. The results demonstrate a significant increase in students’ meaning in life after receiving information services, indicating that the intervention effectively strengthens personal direction, motivation, and resilience. Furthermore, gender comparison analyses reveal that female students experienced greater improvement compared to male students. These findings confirm that information services are a relevant guidance and counseling strategy, particularly in cultural contexts where values and identity play a strong role in adolescent development, such as the Minangkabau community. Keywords: meaning in life, information services, minangkabau adolescents, counseling intervention